The Gut Microbiome Regulates the Psychomotor Effects and Context-Dependent Rewarding Responses to Cocaine in Germ-Free and Antibiotic-Treated Animal Models - Andrew D. Winters; Dina M. Francescutti; David J. Kracht; Diptaraj S. Chaudhari; Branislava Zagorac; Mariana Angoa-Perez (Microorganisms)
Cocaine use disorder remains a major global health concern, with growing evidence that the gut microbiome modulates drug-related behaviors. This study examines the microbiome’s role in cocaine-induced psychomotor activation and context-dependent reward responses using germ-free (GF) and antibiotic-treated (ABX) models. In GF mice, the absence of a microbiome blunted cocaine-induced psychomotor activation (p = 0.013), which was restored after conventionalization. GF mice also showed reduced cocaine-conditioned place preference (CPP) (p = 0.002), which normalized after conventionalization. Dopaminergic function, critical for psychomotor responses and reward, was microbiome-dependent, with increased dopamine levels (p = 0.009) and normalized turnover ratios after conventionalization. In the ABX model, microbiome depletion reduced both cocaine-induced locomotion and CPP responses (p ≤ 0.009), further supporting the role of gut microbes in modulating psychomotor and reward behaviors. ABX-treated mice also showed significant declines in microbial diversity, shifts in bacterial structure, and dysregulation in metabolic, immune, and neurotransmitter pathways (p ≤ 0.0001), including alterations in short-chain fatty acids and gamma-aminobutyric acid metabolism. These findings highlight the gut microbiome’s critical role in regulating cocaine’s psychomotor and rewarding effects, offering insights into potential therapeutic strategies for cocaine use disorder.